2023
DOI: 10.3390/v15020554
|View full text |Cite
|
Sign up to set email alerts
|

Nipah Virus Impairs Autocrine IFN Signaling by Sequestering STAT1 and STAT2 into Inclusion Bodies

Abstract: Nipah virus (NiV) is an emerging zoonotic paramyxovirus that causes fatal infections in humans. As with most disease-causing viruses, the pathogenic potential of NiV is linked to its ability to block antiviral responses, e.g., by antagonizing IFN signaling through blocking STAT proteins. One of the STAT1/2-binding proteins of NiV is the phosphoprotein (P), but its functional role in IFN antagonism in a full viral context is not well defined. As NiV P is required for genome replication and specifically accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…NiV glycoprotein G (NiV-G) has a globular head domain formed of a six-bladed beta-sheet propeller connected via a flexible stalk domain to a transmembrane anchor [10]. The binding of G glycoprotein to its ephrin receptors leads to conformational changes in this glycoprotein, followed by subsequent conformational changes in F glycoprotein that facilitate the fusion of viral and cellular membranes [11,12]. Furthermore, NiV-G/F glycoprotein complexes expressed on infected cell surfaces also facilitate cell-to-cell fusion with neighboring non-infected cells, promoting the spread of infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…NiV glycoprotein G (NiV-G) has a globular head domain formed of a six-bladed beta-sheet propeller connected via a flexible stalk domain to a transmembrane anchor [10]. The binding of G glycoprotein to its ephrin receptors leads to conformational changes in this glycoprotein, followed by subsequent conformational changes in F glycoprotein that facilitate the fusion of viral and cellular membranes [11,12]. Furthermore, NiV-G/F glycoprotein complexes expressed on infected cell surfaces also facilitate cell-to-cell fusion with neighboring non-infected cells, promoting the spread of infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…NiV glycoprotein G (NiV-G) has a globular head domain formed of a six-bladed beta-sheet propeller connected via a flexible stalk domain to a transmembrane anchor [10]. The binding of G glycoprotein to its ephrin receptors leads to conformational changes in this glycoprotein, followed by subsequent conformational changes in F glycoprotein that facilitate the fusion of viral and cellular membranes [11,12]. Furthermore, NiV-G/F glycoprotein complexes expressed on infected cell surfaces also facilitate cell-to-cell fusion with neighboring non-infected cells, promoting the spread of infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…As obligate intracellular parasites, the exploitation of the target cell for its own survival is of utmost necessity, and one of the ways in which it does so is by fighting against the host defense system. Our first article in the issue unveils a mechanism by which the Nipah virus disrupts the autocrine Interferon (IFN) signaling in the infected cells, emphasizing even more the role of inclusion bodies in Nipah infections, a study reported by Becker and Maisner [ 1 ].…”
mentioning
confidence: 99%